Impact of Visual Audio Media on Learning Results on Class XI Reaction Speed Material - Ratman, Ratman; Walanda, Daud Karel; Amalia, Maryam (JEC, 2024)
The study aims to describe the impact of the use of audiovisual media in the form of video learning on the learning results of students at Sigi District State High School 10. The research method is quantitative research with a type of quasi-experimental research or experimental experiment with a design pretest-posttest control group design. The differences in learning results on reaction speed between experimental and control classes are shown by the results of Wilcoxon and Mann Whitney's statistical analysis tests. The results of the Wilcoxons and Mann whitney statistical analytics tests on the post-test values of experimental classes and the control classes both show the significance values Asymp.Sig.(2-tailed) = <0,000. Because of the signification values Asymp.Sig.(2-tailed) = 0,000 < 0,05. Then from the two results of these statistical analyses it can be concluded that there is an influence of the use of audiovisual media in the form of video learning on the learning outcomes of students in SMAN 10 Sigi.